PCA-I and AHP Methods: Unavoidable Arguments in Accident Scenario Classification - H HADEF; M DJEBABRA (J Fail. Anal. and Preven, 2019)
Risk mapping is the foundation of the risk prevention strategy. It allows for the understanding of all factors that may affect the activities. It is a collective decision based on negotiation between the actors. Argument-based negotiation accelerates the negotiation process and converges it toward a final and common decision. It is in this context that this paper aims to illustrate the contribution of the improved PCA and AHP tools, considered as arguments, to the classification of major accident risks.